Changes in In Vivo Glenohumeral Joint Contact Patterns After Arthroscopic Superior Capsule Reconstruction. Issue 7 (31st July 2020) - LeVasseur, Clarissa; Gabrielli, Alexandra; Popchak, Adam; Irrgang, James; Anderst, William; Lin, Albert; Kane, Gillian
Objectives: Patients with irreparable rotator cuff tears (RCT) exhibit functional limitations believed to be caused by superior migration of the humerus1, 2. One viable treatment is superior capsule reconstruction (SCR). SCR has been shown to restore stability of the glenohumeral (GH) joint in cadavers1, but its effectiveness at controlling in vivo humeral motion is unknown. Outcomes are typically evaluated through standard clinical radiographs to assess acromial-humeral distance (AHD), and patient-reported outcomes (PROs) such as ASES and Visual Analog Scale3. Reported changes in AHD are inconsistent, with some studies reporting an increase in AHD of 2.6 to 3.2 mm4, 7, while other studies reported no significant change5, 6 in AHD after SCR. Scapulohumeral rhythm (SHR), a measure of shoulder motion fluidity, has been reported at 2:1 (glenohumeral to scapulothoracic motion) in healthy individuals9, but the effects of SCR on SHR are unknown. The aim of this study was to determine the effect of SCR on static and dynamic AHD, shoulder function, and patient-reported outcomes. We hypothesized that after SCR, static and dynamic AHD would increase, SHR would approximate that of a healthy shoulder, maximum GH abduction would increase, and PROs would improve. Methods: Ten patients with irreparable RCT provided informed consent prior to receiving human dermal allograft SCR. To date, seven (6M, 1F, age 60 ± 8 years) have returned for 1 year post-operative testing. ASES, DASH, and WORC surveys were completed before (PRE), 6 months (6MO-POST), and 1-year after SCR (1YR-POST). Synchronized biplane radiographs of the shoulder were collected PRE and 1YR-POST at 50 images/s while patients performed 3 trials of scapular plane arm abduction. Six degree of freedom GH and scapular kinematics were determined with sub-millimeter accuracy by matching subject-specific CT-based bone models of the humerus and scapula to radiographs using a validated volumetric tracking technique8. AHD was calculated as the minimum distance between the acromion and the humerus at 5° increments of GH abduction. Scapulohumeral rhythm (SHR) was calculated by finding the average change in glenohumeral abduction per degree of scapular upward rotation during scapular abduction.Differences between PRE and 1YR-POST SHR and static AHD distance were evaluated using a paired t-test with significance set at p < 0.05. Changes in PROs were compared to the minimum clinically important difference (MCID). Results: There was a trend toward decreasing static AHD from PRE to 1YR-POST (average decrease: 1.5±1.6mm (p=0.06), however, dynamic AHD did not change from PRE to 1 YR-POST between 45° and 95° of glenohumeral abduction (all p > 0.11) (Figure 1). There was a trend toward increased SHR from 1.1 ± 0.5 PRE to 1.5 ± 0.3 1YR-POST (p = 0.08) (Figure 2), while the increase in maximum GH abduction during scapular abduction from PRE (76.7°±24.5°) to 1YR-POST (91.8°±14.9°) was not statistically significant (p = 0.14) (Figure 2). ASES, WORC, and DASH scores improved beyond the minimum clinically important difference from PRE to 1YR-POST (Table 1) for all patients. Conclusion: In general, SHR tended to more closely resemble that of a healthy shoulder following SCR. Althoughaverage maximum GH abduction was higher postoperatively than preoperatively, that increase was not statistically significant and may reflect that most patients in our cohort had reasonable preoperative abduction. In contrast to those quantitative measures of shoulder function, patient-reported qualitative outcomes all improved significantly. Conflicting results between static and dynamic AHD during higher glenohumeral abduction angles suggest SCR does not appear to affect AHD in higher abduction angles, though the static AHD suggests there may be a difference at lower abduction angles. Dynamic measurements of AHD at lower abduction angles will be necessary to fully characterize the dynamic changes of AHD following SCR. Figure 1. Patient-reported outcomes. Bolded scores represent changes greater than the minimum clinically important different (MCID) compared to PRE and average contact center locations ± 1 standard deviation throughout scapular plane abdjuction. Black + indicates the glenoid center with anterior (A) and posterior (P) directions indicated on the glenoid.